Efficient industrial dye decolorization by Bacillus sp. VUS with its enzyme system - Dawkar, Vishal V.; Jadhav, Umesh U.; Tamboli, Dhawal P.; Govindwar, Sanjay P. (Ecotoxicology and Environmental Safety, 2010)
This work presents role of different enzymes in decolorization of industrial dye Orange T4LL by Bacillus sp. VUS. Bacillus sp. strain VUS decolorized dye Orange T4LL, under static anoxic condition in 24 h. During decolorization of Orange T4LL a significant induction in the activities of lignin peroxidase, tyrosinase, and reductases (NADH-DCIP, azo, and riboflavin) was observed. The biodegradation was monitored by Ultraviolet-visible spectroscopy, Fourier transform infrared spectroscopy, and high performance liquid chromatography. The final products 4-methyl-2-o-tolylazo-benzene-1,3-diamine and [3-(phenyl-hydrazono)-cyclohexa-1,4-dienyl]-methanol were characterized by gas chromatography-mass spectroscopy. Phytotoxicity, COD, and BUD revealed non-toxicity of degraded products. Phytotoxicity study demonstrated non-toxicity of the biodegraded products for crop plants with respect to Triticum aestivum and Sorghum bicolor. Bacillus sp. VUS with its enzyme system could be a useful tool for textile effluent treatment. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: Decolorization; GC-MS; Lignin peroxidase; Orange T4LL; Phytotoxicity; Reductases

Expression of proteins involved in digestion and detoxification are regulated in helicoverpa armigera to cope up with chlorpyrifos insecticide - Dawkar, Vishal V.; Chikate, Yojana R.; More, Tushar H.; Gupta, Vidya S.; Giri, Ashok P. (Insect Science, 2016)
Helicoverpa armigera is a key pest in many vital crops, which is mainly controlled by chemical strategies. To manage this pest is becoming challenging due to its ability and evolution of resistance against insecticides. Further, its subsequent spread on nonhost plant is remarkable in recent times. Hence, decoding resistance mechanism against phytochemicals and synthetic insecticides is a major challenge. The present work describes that the digestion, defense and immunity related enzymes are associated with chlorpyrifos resistance in H. armigera. Proteomic analysis of H. armigera gut tissue upon feeding on chlorpyrifos containing diet (CH) and artificial diet (AD) using nano-liquid chromatography-mass spectrometry identified upregulated 23-proteins in CH fed larvae. Database searches combined with gene ontology analysis revealed that the identified gut proteins engrossed in digestion, proteins crucial for immunity, adaptive responses to stress, and detoxification. Biochemical and quantitative real-time polymerase chain reaction analysis of candidate proteins indicated that insects were struggling to get nutrients and energy in presence of CH, while at the same time endeavoring to metabolize chlorpyrifos. Moreover, we proposed a potential processing pathway of chlorpyrifos in H. armigera gut by examining the metabolites using gas chromatography-mass spectrometry. H. armigera exhibit a range of intriguing behavioral, morphological adaptations and resistance to insecticides by regulating expression of proteins involved in digestion and detoxification mechanisms to cope up with chlorpyrifos. In these contexts, as gut is a rich repository of biological information; profound analysis of gut tissues can give clues of detoxification and resistance mechanism in insects.
Keywords: chlorpyrifos; Helicoverpa armigera; insecticide resistance; proteomics; real-time PCR